VALUASI EKONOMI HUTAN MANGROVE DI DESA TIWOHO KECAMATAN WORI KABUPATEN MINAHASA UTARA - Winda D. Kalitouw; Ribka M. Kumaat; Lyndon R.J. Pangemanan; Paulus A. Pangemanan (Universitas Sam Ratulangi, 2015)
ABSTRACT WINDA DESITHA KALITOUW. Economic Valuation of Mangrove Forets in the Tiwoho Village, Wori District, North Minahasa Regency. Under guidance of Ribka M. Kumaat. , Lyndon R. J. Pangemanan and Paulus A. Pangemanan. This study aims to determine how big the value of the total economic benefits of mangrove forest in the Tiwoho Village of Wori District North Minahasa Regency, by using the concept of economic valuation to calculate the value of the benefits of natural resources which exist. The research was conducted in January to March 2015, by conducting field observations and interviews directly to the community and local government. Based on the results obtained that indicate the area of mangrove forest ecosystems Tiwoho Village with a broad ±62,502 ha, have total value of economic benefits amounted Rp. 2.316.961.823/year with the largest contributor to the value of benefits is from the value of indirect benefits that is the value of the benefits of mangrove forests as a buffer abrasion or sea water waves. The total value of economic benefits can be used as a reference or basic comparison for the community and the government in determining the policy management and utilization of existing mangrove forests. Keyword : valuation economic, mangrove forest ecosystems, benefits value